War and perpetual peace: Hegel, Kant and contemporary war - Maria de Lourdes Borges (Ethic@: an International Journal for Moral Philosophy)
The paper compares the views of two classical authors about the possibility of peace and the inevitability of war: Kant and Hegel. The paper will argue that the main lines of these two schools are still alive today in our contemporary international politics. The Kantian school, with the possibility of peace, based on a league of nations, has inspired the creation of the United Nations. The Hegelian way of thinking (there is no judge above the national states, besides the history of the world) has proven to be as contemporary as ever, once one analyzes some recent events of the international politics. Both Kantian and Hegelian views have weak and strong points, and it is a difficult task to reconcile both of them in a reasonable international politics. At the end, the paper will present JohnRawls´ doctrine of international politics, as stated in The Laws of Peoples, arguing that this doctrine follows the Kantian tradition of a foedus pacificum, while giving room to some Hegelian philosophical conceptions.